2004
DOI: 10.1055/s-2004-832398
|View full text |Cite
|
Sign up to set email alerts
|

Heilungsdauer von Fuß- und Knöchelfrakturen bei Diabetikern: Literaturübersicht und Darstellung eigener Fälle

Abstract: The present data suggest that diabetes mellitus in general does not affect the healing of foot and ankle fractures, provided effective delivery of standard treatment in time. Diabetic complications may affect the outcome. Prospective controlled trials in fracture healing in diabetics are needed to confirm the present evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The latter could not be confirmed in the present study. Boddenberg [4] concluded that ankle fractures in patients with diabetes heal with a significant delay. In a study of Egol et al [11], younger age, male gender, and absence of diabetes were predictive of improved functional recovery at 1 year following ankle fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The latter could not be confirmed in the present study. Boddenberg [4] concluded that ankle fractures in patients with diabetes heal with a significant delay. In a study of Egol et al [11], younger age, male gender, and absence of diabetes were predictive of improved functional recovery at 1 year following ankle fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and experimental studies have shown that diabetes affects fracture healing ( 13 , 20 21 22 ). Diabetes affects the biomechanical properties of bone and results in decreased bone mechanical strength ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Es importante en estos casos un seguimiento cercano del paciente, ya que los pacientes diabéticos que han desarrollado complicaciones crónicas de la diabetes tienen una mayor predisposición a las complicaciones posquirúrgicas 24,27,28,33,34 . En este caso el paciente se mantuvo en descarga absoluta del pie intervenido durante 12 semanas para asegurar una consolidación ósea de manera efectiva y en la posición que se había conseguido en la cirugía, ya que conocemos estudios que muestran el retraso de consolidación ósea de estos pacientes comparados a pacientes sin diabetes [35][36][37][38] . La idea de fondo al tratar estos pacientes es prácticamente "doblar" todos los aspectos de la cirugía con respecto a un paciente no diabético para protegerlo lo más posible, por lo que se utiliza más material de osteosíntesis y se inmoviliza durante más tiempo.…”
Section: Discussionunclassified